Contemporary Albanian Ceramics Exhibition : 16 Albanian Ceramists. - Fyntanides, Serafim (S.l. : Albanian Ministry of Culture : Albanian Association of Ceramists : Panhellenic Association of Ceramists, 1998)
Chrisiko, Christo ; Thomai-Dhamo, Thoma ; Dushku, Fuat ; Gramo, Emira ; Jazexhiu, Keti ; Kadriu, Genci ; Koçi, Sofokli ; Chrisiko, Ergys ; Kuçuku, Mira ; Peqini, Artan ; Prifti, Vlash ; Shima, Ilirian ; Spahija, Sadik ; Thano, Niko ; Turkeshi, Muharrem ; Xoxa, Eli
boek